Moving sport and exercise science forward: A call for the adoption of more transparent research practices - Caldwell, A. R.; Vigotsky, A. D.; Tenan, M. S.; Radel, R.; Mellor, D. T.; Kreutzer, A.; Lahart, I. M.; Mills, J. P.; Boisgontier, M. P.; Consortium for Transparency in Exercise Science (COTES) Collaborators (Sports Medicine, 2020)
The primary means of disseminating sport and exercise science research is currently through journal articles. However, not all studies, especially those with null findings, make it to formal publication. This publication bias towards positive findings may contribute to questionable research practices. Preregistration is a solution to prevent the publication of distorted evidence resulting from this system. This process asks authors to register their hypotheses and methods before data collection on a publicly available repository or by submitting a Registered Report. In the Registered Report format, authors submit a stage 1 manuscript to a participating journal that includes an introduction, methods, and any pilot data indicating the exploratory or confirmatory nature of the study. After a stage 1 peer review, the manuscript can then be offered in-principle acceptance, rejected, or sent back for revisions to improve the quality of the study. If accepted, the project is guaranteed publication, assuming the authors follow the data collection and analysis protocol. After data collection, authors re-submit a stage 2 manuscript that includes the results and discussion, and the study is evaluated on clarity and conformity with the planned analysis. In its final form, Registered Reports appear almost identical to a typical publication, but give readers confidence that the hypotheses and main analyses are less susceptible to bias from questionable research practices. From this perspective, we argue that inclusion of Registered Reports by researchers and journals will improve the transparency, replicability, and trust in sport and exercise science research.